Humours and their Legacy in Early Buddhist Medicine: Revisiting the Indo-European Foundation of Medical Conceptions in the Pāli Canon - Divino, Federico (History of Science in South Asia)

(untitled) (University of Alberta Library, 2025)
In this paper, I analyze the Buddhist humoral theory primarily presented in the suttas of the Pāli Canon through a comparative study with other medical theories developed within the Indo-European tradition, specifically Hippocratic and Āyurvedic medicine. The aim is to trace possible historical developments of a humoral conception that originates from an Indo-European duality between fire and water, with these elements serving as the original core of humoral theory. The text therefore offers a detailed examination of the mechanisms of the three humours in the medical theory as articulated in the Pāli Canon, and draws parallels with Āyurveda and, where possible, with Greek medicine. In Hippocratic medicine, the fundamental elements πῦρ and ὕδωρ are possibly recognized as remnants of an ancient Indo-European binary concept, a concept also preserved in Āyurvedic theory through the universal principles of Agni and Soma, which classify the properties of foods and characteristics of diseases. Can we find similar traces of such a classification in Buddhist humours? By exploring this question, we aim to outline in greater depth the role of humors in the Pāli suttas, enriching our understanding of the archaic medical theory that these suttas bear witness to.